A cohort study of dysmenorrhea and risk of low birth weight. (12th December 2022) - Feng, Baoying; Li, Han; Peng, Yang; Jiang, Qunjiao; Wu, Yanan; Liu, Shun; Zeng, Xiaoyun; Qiu, Xiaoqiang; Huang, Dongping
Abstract: Objective: Little is known about the association between maternal history of dysmenorrhea and perinatal outcomes. The aim of this study was to investigate the association between maternal history of dysmenorrhea and low birth weight (LBW). Methods: A total of 6754 pregnant women were recruited from the ongoing prospective cohort study in Guangxi, China, in 2015–2018. Information on the maternal history of dysmenorrhea was obtained by questionnaires including visual analog scale (VAS) questions during the first antenatal care visit. The association of maternal history of dysmenorrhea and LBW was evaluated using logistic regression analyses adjusted for confounding factors (infant sex, maternal age, parity, pre-pregnancy body mass index (BMI) (kg/m 2 ), gestational age, alcohol use during pregnancy, passive smoking, and occupational status). Results: Mothers with a history of dysmenorrhea were more likely to give birth to LBW infants (adjusted odds ratio (OR)=1.44; 95% confidence interval (CI): 1.12, 1.83). Among women with a history of dysmenorrhea, women ≥29 years old (adjusted OR 1.46; 95% CI 1.02, 2.10), multiparous (adjusted OR 1.59, 95% CI 1.12, 2.25), and women gave birth to female infant (adjusted OR = 1.53, 95% CI = 1.11, 2.11) had a higher risk of LBW. Conclusions: As the first cohort study to investigate the association between maternal history of dysmenorrhea and LBW, our study shows that dysmenorrhea may increase the risk of LBW.